2010
DOI: 10.1089/dia.2009.0157
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitoring in Subjects After Simultaneous Pancreas-Kidney and Kidney-Alone Transplantation

Abstract: Background: Simultaneous pancreas-kidney (SPK) transplantation is an important replacement therapy for individuals with diabetes and end-stage renal disease. Kidney-alone (KA) transplantation is associated with a high incidence of post-transplant diabetes.Methods: This was a cross-sectional study. We studied 48-h glucose concentrations in eight subjects with type 1 diabetes mellitus after SPK transplantation, six subjects post-KA transplantation, and nine healthy controls using the CGMS Ò (Medtronic Minimed, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 25 publications
2
23
0
7
Order By: Relevance
“…12 So, data of this small study do not allow us to conclude about glucose metabolism in adrenal-insufficient patients who are receiving chronic replacement-either for hypoglycemia episodes due to chronic cortisol deficiency or for hyperglycemia episodes due to chronic overtreatment.…”
Section: Cgms In Patients With Addison's Disease 387 Conclusionmentioning
confidence: 83%
“…12 So, data of this small study do not allow us to conclude about glucose metabolism in adrenal-insufficient patients who are receiving chronic replacement-either for hypoglycemia episodes due to chronic cortisol deficiency or for hyperglycemia episodes due to chronic overtreatment.…”
Section: Cgms In Patients With Addison's Disease 387 Conclusionmentioning
confidence: 83%
“…Yates et al demonstrated using CGM that divided dosing of prednisone reduced glycemic variability in renal transplant recipients [50]. Two studies, one in children and one in adults, described the usefulness of CGM in KTRs to detect hyperglycemic episodes that would have remained undetected by routine laboratory testing [51,52]. Wojtusciszyn et al showed in nondiabetic patients immediately after kidney transplantation that mean glucose levels determined by CGM are elevated in nearly every patient and that the degree of hyperglycemia in this early phase might help identify patients at risk for later development of PTDM and graft failure [53].…”
Section: Continuous Glucose Monitoring (Cgm)mentioning
confidence: 99%
“…İmmünosupresif tedaviler açısından yapılan bir çalışmada EBPN grubunda greft sağkalımı açısından tacrolimusun siklosporinden üstün olduğu, akut rejeksiyonun önlenmesinde ise mikofenolik asid türevlerinin azathioprine'den daha üstün olduğu gösterilmiştir (9). Çalışmamızda da EBPN grubunda hastaların %95'inde tacrolimus+mikofenolik asid türevleri kullanılmış ve başarılı sonuçlar alınmıştır.…”
Section: Bulgularunclassified
“…EBPN'nin tek başına böbrek nakline göre şeker kontrolü açısından oldukça üstün olduğu gösterilmiştir (9). Çalışmamızda, açlık kan şekeri ve HbA1c düzeylerinin EBPN grubunda daha iyi olduğu, böbrek işlevleri ve proteinüri açısından ise gruplar arasında fark olmadığı gösterilmiştir.…”
Section: Bulgularunclassified